(النكاح العرفي وآثاره في الإرث (دراسة حالة قرية بوكوان، سمارندا - Agus Nurdiansyah; Dian Berkah (Universitas Muhammadiyah Surabaya, 2020)
Closed marriage is one of the many events that occur in all regions in Indonesia.One of them is in Bukuan Village, Palaran, Samarinda.There are still residents of Bukuan who have a marriage without registering it in the KUA and have not legalized the marriage, thus affecting the implementation of inheritance.From the background of the problem, the writer formulates the problem into 2, namely 1) what are the consequences of the law of marital marriage in inheritance? 2) how is the implementation of inheritance in closed marriage in Bukuan Village?This research is a qualitative research conducted with a case study approach. Data collection techniques are done by observation, interviews, and documentation. Data were analyzed in a qualitative descriptive manner.The results of this study indicate that the legal consequence of closed marriage in inheritance is changing the rights of heirs in inheritance and influencing the distribution of inheritance in a family as a result of closed marriage in Bukuan, where assets are distributed equally before the heir dies or the property is distributed in an equal manner. evenly distributed after the heir died after using the distribution of Islamic legal inheritance or without using the division of Islamic legal inheritance first. Keywords: closed marriage, inheritance, legal consequences